2009
DOI: 10.1007/s11934-009-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

A new look at detrusor underactivity: Impaired contractility versus afferent dysfunction

Abstract: Detrusor underactivity (DU) is a clinical condition that describes a bladder dysfunction marked by failure of the bladder to generate sufficient contraction strength to empty over a reasonable time period. DU affects both the elderly and patients with disease processes such as diabetes mellitus. Once assumed to be a motor contractility problem, the etiology of DU now appears to be more dynamic, necessitating a new look at afferent dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
1
26
0
2
Order By: Relevance
“…Similar findings in autonomic nerve innervation were observed in human bladder with bladder outlet obstruction . The data may show the contribution of insufficient activation of cholinergic neurons to the decreased contractility of detrusor muscles . Using human detrusor smooth muscle strips, we also demonstrated that the cholinergic component of electrical field simulation‐induced contraction was significantly decreased with aging, and that there was significant negative correlation between cholinergic contraction and aging …”
Section: Efferent Dysfunction and A Decrease Of Detrusor Muscle Contrsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings in autonomic nerve innervation were observed in human bladder with bladder outlet obstruction . The data may show the contribution of insufficient activation of cholinergic neurons to the decreased contractility of detrusor muscles . Using human detrusor smooth muscle strips, we also demonstrated that the cholinergic component of electrical field simulation‐induced contraction was significantly decreased with aging, and that there was significant negative correlation between cholinergic contraction and aging …”
Section: Efferent Dysfunction and A Decrease Of Detrusor Muscle Contrsupporting
confidence: 80%
“…Currently, it has been suggested that DU may result from disturbances of not only the detrusor but also sensory afferent pathway, central nervous systems (CNS), and motor efferent nerves (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of DU is multifactorial, and many diseases or disorders can cause DU [24]. Long term of single bladder outlet obstruction can impair detrusor contractility leading to the decrease of the contractility [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cukorbetegség során kialakult neuropathia a vizelé-si reflex csökkenéséhez, illetve megszűnéséhez vezethet [14]. Tanulmányunkban egyértelmű összefüggést mutattunk ki a BCI csökkenése és neurológiai kórképek, diabetes között (p = 0,042, p = 0,008).…”
Section: Megbeszélésunclassified